Kesehatan Mental Tenaga Kesehatan Pada Kondisi Pandemi COVID-19: Literature Review - Reliani, Reliani (Jurnal Keperawatan Muhammadiyah, 2020)
In the Covid-19 pandemic situation, health workers are the front line officers who are directly involved in the treatment and care of patients. With the number of suspected positive confirmed cases continuing to increase, the workload of health workers increases so that there can be an increase in feelings of hopelessness, feelings of fear of being infected due to a lack of personal protective equipment, the amount of certain drugs, so that it can have an impact on the mental health of health workers. Objective: to describe previous studies regarding mental health conditions, causes of mental health disorders, and efforts to treat health workers during the Covid-19 pandemic. Method: The journal literature review discusses the mental health of health workers during the Covid-19 pandemic. Search articles via the internet with the Pubmed database, full text, 2020-2021. Results: the most symptoms experienced by health workers during the Covid-19 pandemic were symptoms of anxiety, symptoms of depression, and insomnia, distress, PTSD, and psychological disorders. Conclusion: The mental health of health workers in the Covid-19 pandemic conditions experienced symptoms of depression, anxiety, insomnia, distress, stress, and PTSD caused by psychological pressure during the pandemic such as feeling worried about being infected with yourself, family, and people around remembering that health workers do direct contact with Covid-19 patients, the spread of the virus, increased workload, lack of physical and mental rest, stigmatization, lack of drugs, personal protective equipment, virus control and evidence-based interventions.